Vitamin E deficiency induced neurological disease in common variable immunodeficiency: two cases and a review of the literature of vitamin E deficiency. - Aslam, A; Misbah, SA; Talbot, K; Chapel, H (2004)
Vitamin E deficiency causes a neurological disorder characterised by sensory loss, ataxia and retinitis pigmentosa due to free radical mediated neuronal damage. Symptomatic vitamin E deficiency has been reported in genetic defects of the vitamin E transport protein and in malabsorption complicating cholestasis, abetalipoproteinaemia, celiac disease, cystic fibrosis and small bowel resection. There are no reports to date of vitamin E deficiency in patients with primary immunodeficiencies. We describe two CVID patients with the associated enteropathy who developed neurological disease because of vitamin E deficiency, suggesting a possible predisposition to developing this complication. We recommend that all CVID patients with evidence of an enteropathy be screened for vitamin E deficiency, as early detection and consequent treatment may prevent, halt or reverse the neurological sequelae.